Identification and validation of optimal process conditions for protein enrichment of seaweed (Ulva Spp.) by Phanerochaete chrysosporium in a reactor - Jamal, Parveen; Saheed, Olorunnisola Kola; Jaswir, Irwandi; Tijani, Ruqayyah I. D. (Kulliyyah of Engineering, 2016)
Solid state bioconversion (SSB) of seaweed for protein enrichment was conducted over 7-day period using Phanerochaete chrysosporium (P. chrysosporium). One-factor-at-a-time (OFAT) optimization of process parameters revealed 70% for moisture content, 9% for inoculum size and 7% for minerals. Optimum substrate depth in 1 kg reactor was 12 mm and the protein increased to 107.89 mg/g. Fourier transformation infrared spectroscopy (FTIR) analysis showed modifications in the polysaccharide resulting from SSB. Soluble and reducing sugars concentrations improved by 168.88% and 198.95%, while total carbohydrate reduced to 107.15±1.21mg/g.